Kelakai (Stenochlaena palustris (Burm.) Bedd) Extract from Kalimantan: Determination of Total Phenol and Alkaloid Content Potential as Nutraceuticals - Kiki Rizky Ananda; Muthmainah; Nur Hafidha Hikmayani (Postgraduate, University of Mataram, 2025)
Degenerative diseases such as diabetes, hypertension, and cancer have become health problems in the world. Currently, plants that have bioactive compounds are an alternative for preventing and treating health problems. Kelakai plants are one of the plants that are commonly consumed as a vegetable by Kalimantan. In addition to having nutritional content, kelakai also has bioactive compounds, namely phenols and alkaloids. However, thus far, the total content in the extract of kelakai leaves and stems remains unknown. Therefore, in this study, a test was conducted on the total phenols and alkaloids of the extract of kelakai leaves and stems from Central Kalimantan, Indonesia. This study is a quantitative study with a laboratory experimental method. The extraction method used is maceration with 70% ethanol solvent. Measurement of alkaloids and phenols utilized the spectrophotometric method. The study showed that the extract of kelakai leaves and stems has a total phenol content of 56,180+0.81 mg GAE/g and alkaloids of 86,524+0.522 ppm so it has the potential as a nutraceutical. The results of kelakai extract test can be a reference for pre-clinical research as a plant that not only has nutritional content but also bioactive compounds.